The identification of homogeneous groups of cattle farms in the mountains of León, Spain - Serrano Martínez, E.; Giráldez García, F.J.; Lavín González, P.; Bernués Jal, A.; Bernués Jal, A.; Ruiz Mantecón, A. (Spanish Journal of Agricultural Research, 2004)
The aim of this work was to establish homogenous groups of cattle farms in the mountains of León, Spain, using the variables selected in a sister paper (this issue). Principal components analysis (PCA) was used to characterise and compare the different farms studied. Two classifications were established, the first taking into account the first seven axes selected by PCA, and the second by taking into account only the first two. A comparison of these systems led to the latter being selected. The final classification system involves eight groups based mainly on the orientation of production, size, productivity per breeding cow, and productivity per work unit.